(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2020)
In this paper, the BluePrint continuous improvement tool is proposed to optimize the accounts receivable process in the services company Districarga Los Andes CA, for which a field descriptive investigation was carried out, with information collection through direct observation, documentary review and the application of a questionnaire of fifteen (15) items addressed to study the elements determined in the specific objectives. With the diagnosis made it was determined that the company performs collection procedures without an established manual, with procedures carried out empirically, without order or registration, which leads to accumulations or accounts that are kept for non-acceptable periods of time. On the other hand, an outdated customer database was observed with difficulty in its location to carry out the collections. That is why the service map "Service Blueprint" is proposed, which includes interactions between customers and companies in relation to the collection of invoices generated within the provision of the service.